Thermostable alkaline phosphatase in bacteria and archaea at a glance - Hamzah, Haider Mousa (Sulaimani Journal for Pure and Applied Sciences, 2019)
Alkaline Phosphatase (AP) is one of the most ubiquitous enzymes for the dephosphorylation of nucleic acids in molecular biology; as reporter enzymes for secreted proteins; for colorimetric immunoassays; and as an indicator of activity in research and diagnostic kits. Today, there are continuing efforts suggesting the possibility of producing unique AP from thermophilic bacteria and archaeal cells. As AP is found in a few members of thermophiles, it is also anticipated that it will be detected in their siblings, yet the reason behind the variation in their AP activities is ambiguous. This mini review provides a comprehensive survey of the bacterial and archaeal alkaline phosphatases with particular emphasis on the thermostable APs from the members of thermophiles and their activity variation.
Keywords: Alkaline phosphatase; Archaea; Hyperthermophile; Thermophiles